Bioactive glasses beyond bone and teeth: Emerging applications in contact with soft tissues - Miguez Pacheco, Valentina; Hench, Larry L.; Boccaccini, Aldo R. (Acta Biomaterialia, 2015)
The applications of bioactive glasses (BGs) have to a great extent been related to the replacement, regeneration and repair of hard tissues, such as bone and teeth, and there is an extensive bibliography documenting the role of BGs as bone replacement materials and in bone tissue engineering applications. Interestingly, many of the biochemical reactions arising from the contact of BGs with bodily fluids, in particular the local increase in concentration of various ions at the glass-tissue interface, are also relevant to mechanisms involved in soft tissue regeneration. An increasing number of studies report on the application of BGs in contact with soft tissues, aiming at exploiting the well-known bioactive properties of BGs in soft tissue regeneration and wound healing. This review focuses on research, sometimes involving preliminary in vitro studies but also in vivo evidence, that demonstrates the suitability of BGs in contact with tissues outside the skeletal system, which includes studies investigating vascularization, wound healing and cardiac, lung, nerve, gastrointestinal, urinary tract and laryngeal tissue repair using BGs in various forms of particulates, fibers and nanoparticles with and without polymer components. Potentially active mechanisms of interaction of BGs and soft tissues based on the surface bioreactivity of BGs and on biomechanical stimuli affecting the soft tissue-BG collagenous bonding are discussed based on results in the literature. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Bioactive glasses; Soft tissue engineering; Vascularisation; Wound healing